A consistent analysis of diversification decisions with non-observable firm effects - Merino, Fernando; Rodríguez, Diego (Strategic Management Journal, 1997)
The empirical analyses of firm diversification decisions, both for new activities (new products) and markets (for example, new routes for airlines), have usually estimated a binary dependent variable model for each of the decisions the firm makes. To obtain consistent estimators, every relevant effect must be considered in the specification. As this will hardly happen, the presence of nonobserved firm effects (either because such data do not exist or because it is impossible to obtain them) must be econometrically treated, because it causes inconsistency in the estimations. In this paper we propose to use the estimators provided by the maximization of the conditional likelihood function in problems of this kind because they give consistent results even when unobserved firm effects are present. Finally, we apply this technique to an example of diversification among Spanish manufacturers. © 1997 John Wiley & Sons, Ltd.